Isolating and Characterizing Phosphorus Solubilizing Bacteria From Rhizospheres of Native Plants Grown in Calcareous Soils - Li, Krystal S.; Zeghbroeck J., Van; Liu, Qingchun; Zhang, Shouan (Frontiers in Environmental Science, 2021)
Many soils including urban soils have high legacy soil P due to repeated applications of P fertilizers, but almost all legacy soil P is fixed by calcium in the calcareous soils. Phosphorus solubilizing bacteria (PSB) have the ability to transfer fixed (non-labile) soil P into plant available P. The aim of this study was to isolate P solubilizing bacteria from the rhizospheres of four local native plants [broomsedge bluestem (Andropogon virginicus), giant sword ferns (Nephrolepis biserrata), sawgrass (Cladium jamaicense), and sea ox-eye daisy (Borrichia frutescens)] grown in low P calcareous soils and sediments and to determine their ability to solubilize P. A total of 44 strains of PSB were isolated with 15 of them being identified by sequencing the 16S rRNA genes as Bacillus flexus, Beijerinckia fluminensis, Enterobacter ludwigii, Enterobacter sp., and Pantoea cypripedii. After a seven-day incubation, these strains reduced pH to <4.27 and increased water-soluble P up to 588 mg L-1. Enterobacter ludwigii shows superior P solubilizing ability amount PSB isolated. Therefore, the isolated strains from the local native environment have the potential to thrive in local calcareous soils and possess a strong ability to transform non-labile P into bioavailable forms for plants to uptake.